(untitled) (Journal of Atomic and Molecular Sciences, 2017)
Laser induced dissociation control of the symmetric diatomic molecular ion H_2^+ and the triatomic molecular ion H_3^2+ is discussed. The simulation results demonstrate that a long-wavelength terahertz or mid-infrared laser pulse can be used to control the electrons of the dissociative states after the excitation of an ultrashort ultraviolet (UV) laser pulse. For H_2^+, there exists an effective time, which increases with increasing pulse duration of the UV laser pulse, for controlling the molecular dissociation. For the electrons of the 1sσ_g state, they move along the polarization direction of the dissociation control electric field. In contrast, for the electrons of the 2pσ_u state, they move in the opposite direction to that of the electric force. And for the triatomic molecule H_3^2+, the electron dissociation control can also be realized by changing the central wavelength of the exciting UV pulse.